2012
DOI: 10.4103/0970-2113.102799
|View full text |Cite
|
Sign up to set email alerts
|

Perception of tuberculosis among general patients of tertiary care hospitals of Bengal

Abstract: Introduction:Tuberculosis is a public health problem in India. The patients of Tuberculosis hide their disease from family, relatives, and community due to the presence of stigma. This study was conducted to assess the knowledge, awareness, and perception regarding social variables of tuberculosis among patients and to associate the awareness with their literacy status.Materials and Methods:Type of study was observational, descriptive, and epidemiological. Study design was cross-sectional. Study setting was ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
4
12
0
1
Order By: Relevance
“…The present study conducted among 220 pulmonary tuberculosis patients revealed that majority of the patients had heard of tuberculosis prior to acquiring it; and the major source of information were community and health personals followed by media. This is consistent with a study conducted in Bengal by Das P et al 5 which showed that 91.30 percent of the patients had the acquaintance prior to acquiring the disease and the source of information was mostly from community. Again in another study conducted in Vietnam 6 93 percent of the patients had information regarding tuberculosis from health worker followed by media.…”
Section: Discussionsupporting
confidence: 91%
“…The present study conducted among 220 pulmonary tuberculosis patients revealed that majority of the patients had heard of tuberculosis prior to acquiring it; and the major source of information were community and health personals followed by media. This is consistent with a study conducted in Bengal by Das P et al 5 which showed that 91.30 percent of the patients had the acquaintance prior to acquiring the disease and the source of information was mostly from community. Again in another study conducted in Vietnam 6 93 percent of the patients had information regarding tuberculosis from health worker followed by media.…”
Section: Discussionsupporting
confidence: 91%
“…13,14 Moreover, lack of awareness can worsen the epidemiological situation by increasing drug resistant patients, who may increase the risk of infection with drug-resistant bacilli. 12 Literature review revealed that some studies in India have been done to understand the knowledge and awareness about TB both in patient [15][16][17] and in general populations. 18,19 However, to best of our knowledge, study related to knowledge and awareness about TB among TB patients of rural areas of West Bengal is yet to be made.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The main reason for social stigma in India is lack of knowledge and awareness about the disease per se. [7] Therefore to achieve the goal/ objective of RNTCP the need for creating awareness about etiology, symptoms, mode of spread and source of infection etc. is needed.…”
Section: Global/ Burden In Indiamentioning
confidence: 99%
“…A study done in Bengal revealed only 2% of general population in hospital knew about DOTS. [17] Considering the curability of the disease only 53.10% thought that TB is curable. A similar study done in Serbia reported that 86% thought TB is curable and another study at Rajasthan said 90% were in view of TB being a curable disease.…”
Section: Study Populationmentioning
confidence: 99%